The phonesthetics of blends: A lexicographic study of cognitive blends in the OED - Smith Chris (ExELL (Explorations in English Language and Linguistics))
This preliminary study of 285 morphological and cognitive blends (attestation dates 1200-2012) aims to investigate the role of phonesthemes in the structuring of the English lexicon. A study of OED word origins shows a disparity between older (1200-1900) and recent blends (1903-2012). Sound symbolism plays an overriding role in over 50% of older blends, leading to a study of initial phonesthemes (i.e. consonant clusters). Several case studies of diachronic semantic shift attested in the OED point to the existence of multidirectional motivation ties. This preliminary study supports the psycholinguistic theory that 1) there is a structured secondary sound symbolism in English, and that 2) it is still productive today and may play a role in the creation of neologisms as well as ensuring their survival (see Bergen, 2010: 52). A more in-depth usage-based analysis using sophisticated measurement tools is the next step in the study.